Variation of some atmospheric circulation factors affecting Vietnam climate - Nguyen, Van Thang (VNU, 2014)
More and more evidence of global climate warming, sea level rise, droughts, floods and climate extremes are recorded. In Vietnam, the manifestation of climate change (CC) is often considered as changing the level and trend of variation of main climatic elements and sea level. However, Vietnam climate influenced by the characteristics of atmospheric circulation in the Earth climate system. This paper presents expression of some characteristics of regional (the expanded East Asia area: 10 0 S - 50 0 N; 60 0 E - 160 0 E) atmospheric circulation affecting Vietnam climate, including: surface pressure, zonal circulation indices (Iς); meridional circulation indices (Iλ); Cold front frequency (CF) in the North of Viet Nam. The numbers of tropical cyclone over the East Sea and affecting Vietnam are mentioned in other studies. Changes in atmospheric circulation over the area are reflected by the differences of regional atmospheric circulation characteristics values between the recent period (1991-2007) and the study period (1960-2007) mentioned above.